2013
DOI: 10.5455/vetworld.2013.337-342
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enrofloxacin on zootechnical performance, behaviour and immunohistopathological response in broiler chicken

Abstract: Aim: A safety pharmacology trial was conducted to evaluate the impact of enrofloxacin on zootechnical performance, behaviour and immunohistopathological response in Newcastle disease virus vaccinated broiler chicken after pulsed water medication. Materials and Methods: Experimental group birds were administered with enrofloxacin at recommended therapeutic dose 10mg/Kg body weight, through drinking water for five consecutive days from 43rd to 47th day of age. Zootechnical performance parameters, behavioural and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
2
3
0
Order By: Relevance
“…This study confirms previous observations that the early short-term administration of antibiotics or MON in the recommended doses does not compromise the growth performance of birds ( Watkins et al, 1993 ; Watkins and Novilla, 1994 ; Chapman and Saleh, 1999 ; Sureshkumar et al, 2013 ). However, Madubuike et al (2020) reported that DOX administered in early life to vaccinated chickens decreased their BW gain.…”
Section: Discussionsupporting
confidence: 91%
“…This study confirms previous observations that the early short-term administration of antibiotics or MON in the recommended doses does not compromise the growth performance of birds ( Watkins et al, 1993 ; Watkins and Novilla, 1994 ; Chapman and Saleh, 1999 ; Sureshkumar et al, 2013 ). However, Madubuike et al (2020) reported that DOX administered in early life to vaccinated chickens decreased their BW gain.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, enrofloxacin showed no negative effect on the immune response to NDV in chickens of Farm 7 during this study (Group I). On the contrary, Sureshkumar et al (2013) confirmed that the significant reduction in HI antibody titers against NDV of enrofloxacin administered birds was found. According to previous studies, a high proportion of birds (> 85%) with a high antibody titre (≥ 3log 2 ) after vaccination will ensure that no epidemic spread is possible in vaccinated population (Kapczynski & King, 2005;Boven et al, 2008).…”
Section: Resultssupporting
confidence: 57%
“…The control group received non-medicated water and normal feed (without Se NPs), treatment group II were medicated with EFX (M/s. Neospark Drugs and Chemicals Private Limited, Hyderabad, India) at a recommended therapeutic dose of 10 mg per kg body weight, in drinking water from day thirty-two to forty-two 8,21 and fed on a normal diet (without Se NPs). Birds received their freshly-prepared daily medication during a 4 h period in the morning, and their water was antibiotic-free for the remaining 20 h in the day.…”
Section: Experimental Designmentioning
confidence: 99%
“…A suitable weight of the fresh tissue (5 g) was homogenized in (50 mL) ice-cold phosphate buffer saline ( pH ∼ 7), and then the homogenate was centrifuged for 10 min at 4 °C for the estimation of antioxidant assay. 8…”
Section: Sampling and Preparationmentioning
confidence: 99%
See 1 more Smart Citation